2013
DOI: 10.1007/s11606-013-2433-1
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Pharmacologic Treatments for Episodic Migraine in Adults

Abstract: ELIGIBILITY CRITERIA: English-language randomized controlled trials (RCTs) of preventive drugs compared to placebo or active treatments examining rates of ≥50 % reduction in monthly migraine frequency or improvement in quality of life. STUDY APPRAISAL AND SYNTHESIS METHODS:We assessed risk of bias and strength of evidence and conducted random effects meta-analyses of absolute risk differences and Bayesian network meta-analysis. RESULTS: Of 5,244 retrieved references, 215 publications of RCTs provided mostly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 135 publications
(107 reference statements)
2
65
1
2
Order By: Relevance
“…However, only about half of migraineurs have clinically meaningful responses to preventive drug treatments, more than 10% discontinue due to adverse events, 1 and half report dissatisfaction with their current treatment strategies. However, only about half of migraineurs have clinically meaningful responses to preventive drug treatments, more than 10% discontinue due to adverse events, 1 and half report dissatisfaction with their current treatment strategies.…”
mentioning
confidence: 99%
“…However, only about half of migraineurs have clinically meaningful responses to preventive drug treatments, more than 10% discontinue due to adverse events, 1 and half report dissatisfaction with their current treatment strategies. However, only about half of migraineurs have clinically meaningful responses to preventive drug treatments, more than 10% discontinue due to adverse events, 1 and half report dissatisfaction with their current treatment strategies.…”
mentioning
confidence: 99%
“…Randomized controlled studies of 59 drugs from 14 drug classes have demonstrated some value of preventive treatment for episodic chronic migraine headache. 26 Such medications may decrease the frequency of migraine up to 50%. Although employees of the company in the current study had access only to a CDHP, most of these migraine drug classes are now generic and available at low cost.…”
Section: Discussionmentioning
confidence: 99%
“…For migraine prophylaxis, meta-analyses support the efficacy of approved drugs including topiramate and valproate [115,116] and off-label TCAs, particularly amitriptyline [115,117]. There is limited evidence for the use of some other antidepressants, including venlafaxine [115], but clomipramine is considered ineffective in migraine prophylaxis [23].…”
Section: Newer Antidepressantsmentioning
confidence: 99%